2006
DOI: 10.4141/p05-036
|View full text |Cite
|
Sign up to set email alerts
|

Managing nitrogen fertility of irrigated soft white spring wheats for optimum quality

Abstract: . Managing nitrogen fertility of irrigated soft white spring wheats for optimum quality. Can. J. Plant Sci. 86: 459-464. Irrigated wheat growers often choose to apply only part of the crop's nitrogen fertilizer requirement at planting to avoid over-fertilizing the crop at early stages of growth. Later in the growing season, producers will apply additional nitrogen fertilizer as needed to optimize production. This study evaluated effects of top-dress nitrogen fertilizer application timing and rate on the millin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Wheat classes have specific grain quality requirements based on their intended end use (Guttieri et al, 2005). Six classes of wheat are grown under diverse growing conditions in the United States (US Wheat Associates, 2018).…”
mentioning
confidence: 99%
“…Wheat classes have specific grain quality requirements based on their intended end use (Guttieri et al, 2005). Six classes of wheat are grown under diverse growing conditions in the United States (US Wheat Associates, 2018).…”
mentioning
confidence: 99%
“…A number of studies have found significant genetic variation for flour protein concentration and cookie diameter (Guttieri et al, 2003; Souza et al, 2004; Breseghello et al, 2005). Yet, flour protein concentration is strongly influenced by a range of environmental effects that modulate the grain yield per area and the soil nitrogen fertility (Souza et al, 2004; Guttieri et al, 2006). Flour protein can be used in some cases as a covariate to reduce genotype × environment interaction for cookie diameter that may be caused by large environmental differences in flour protein concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat grain samples of soft red winter wheat were produced in replicated, randomized fi eld plots (4.2 m 2 ) as part of Virginia Tech's statewide testing program of new cultivars and elite prerelease lines. Grain samples harvested from Painter, VA (2002 and, Blacksburg, VA (2004), and Warsaw, VA (2005and 2006 having no obvious pre-harvest sprouting present or grain diseases such as Fusarium head blight (causal organism Fusarium graminearum Schwabe) were submitted for quality analyses. In 2005, initial grain inspection and production conditions supported an absence of pre-harvest sprouting in the samples.…”
Section: Wheat Samplesmentioning
confidence: 99%
See 1 more Smart Citation